2010
DOI: 10.1007/s11999-009-1034-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Femoral Component Loosening Predispose to Femoral Fracture?: An In Vitro Comparison of Cemented Hips

Abstract: The incidence of femur fracture around total hip arthroplasties continues to increase at substantial cost to society. These fractures are frequently associated with a loose femoral component. Consequently, we sought to test whether femoral component loosening predisposes to periprosthetic femoral fracture. Because many periprosthetic femoral fractures are spiral in nature, we evaluated the torsional characteristics of the implanted femur in which the only design variable was instability of the femoral componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
(48 reference statements)
1
18
2
3
Order By: Relevance
“…Furthermore, aseptic loosening has been shown to be an important risk factor for this fracture after cemented THR. 2,22,41,[44][45][46] Although two hips showed significant osteopenia of the proximal femur at the time of fracture, in our study using uncemented stems we did not find pre-fracture evidence of loosening of the femoral component at the last follow-up examinations. At the last clinical and radiological evaluation before peri-prosthetic femoral fracture, all the stems were considered to be well fixed.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, aseptic loosening has been shown to be an important risk factor for this fracture after cemented THR. 2,22,41,[44][45][46] Although two hips showed significant osteopenia of the proximal femur at the time of fracture, in our study using uncemented stems we did not find pre-fracture evidence of loosening of the femoral component at the last follow-up examinations. At the last clinical and radiological evaluation before peri-prosthetic femoral fracture, all the stems were considered to be well fixed.…”
Section: Discussioncontrasting
confidence: 53%
“…[18][19][20][21]25 Risk factors for periprosthetic femoral shaft fractures about hip arthroplasty femoral stems are related to the age of the patient, gender, index diagnosis, presence or absence of osteolysis, presence or absence of aseptic loosening, primary or revision status, the specific type of implant used, and whether cemented or noncemented technique was used. 24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] Identifying risk factors can both improve patient counseling and potentially improve efforts at fracture prevention.…”
Section: Vancouver B and C Fractures Incidence And Risk Factorsmentioning
confidence: 99%
“…This has been borne out in biomechanical studies in synthetic and cadaveric femora. 18 Early detection of osteolysis and loosening of femoral components, by routine clinical and radiographic follow-up, may limit the incidence of periprosthetic fracture. 16 In one study, the authors found that 70% of the stems were considered to be loose at the time the patient sustained the fracture.…”
Section: Fractures About Hip Arthroplastymentioning
confidence: 99%